P-017 Intermediate catheters: experience, cost and complication rates at two high volume centers. (12th July 2011) - Hui, F; Cawley, M; Dion, J; Rasmussen, P; Moskowitz, S; Toth, G; Hussain, S; Schuette, J; Spiotta, A; Tong, F
Abstract : Introduction: Stable access to target lesions is foundational to endovascular therapy, be it in hemorrhagic or ischemic disease. Continued evolution in access technology has resulted in next generation catheters that afford improved trackability, as well as distal and proximal support. Neuron guide catheter family and the Concentric Outreach Distal Access Catheter fall into this category of hybrid catheters. Both families of devices possess overlapping characteristics allowing operators to achieve a more stable proximal access complex. Methods: A retrospective review of 608 cases in which an intermediate catheter was used during 2008–2010 at Cleveland Clinic (Cleveland, OH) and throughout 2010 at Emory University Hospital (Atlanta, GA) was conducted, and the cases classified by indication. Catheter placement, distal most location and related complications were recorded and experience summarized. We also review the differences in the catheters and the rationale for catheter selection, as well as relative costs for each approach. Results: A total of 311 Neuron 053, 166 Neuron 070, 36 DAC 3.9 Fr, 61 DAC 4.3 Fr, and 34 DAC 5.2 Fr catheters were deployed. Of these, 459 placements were in the anterior circulation, 130 in the posterior circulation, 11 in the external carotid artery, and eight were used intravenously. Abstract P-017 table 1 summarizes the clinical scenarios where the catheters were used, Abstract P-017 table 2 the distal most placements, Abstract P-017 table 3 the complications and Abstract P-017 table 4 the estimated costs for a typical catheter selection. Complication rates were 9/131 (6.9%) for the DAC catheter group, 16/311 (5.1%) for the Neuron 053 group, and 14/166 (8.4%) for the Neuron 070 group with p=0.37, χ 2 test Abstract P-017 table 5 . Conclusion: Next generation access catheters possess characteristics that blend qualities of traditional microcatheters and guide catheters. These "intermediate catheters" represent a class of access devices that allow for better catheter support, and allow for multi-axial access techniques. The utility of these catheters must be balanced against costs. The increased procedural complexity involved in using multi-axial techniques should also be a consideration, but judicious application should prove beneficial to patients. There is no statistically significant difference in complication rates when using these catheters as well as comparable complication rates when compared to historical complication rates quoted to patients.